Scientific outreach and initial teaching training: an experience in the prison - Versolato, Marina Savordelli (2021)
The Science Stand (SS) is an interdisciplinary proposal of non-formal actions of dialogical and critical communication of science for children, adolescents, and the general public in school and non-school educational spaces. In addition to the fixed stands, we sought to find an itinerant, simple, and versatile way to be used in various places and moments, with or without the stands, composed of standardized easels and tops, which led to greater mobility of the project activities. SS has as one of its concerns the training of mediators to act in the processes of scientific outreach. This article aims to investigate the contributions, for future teachers, of the performance as mediators of processes in the context of itinerant scientific outreach - in this case, the Science Stand - with scientific experiments in the context of prison. To this end, we observed the interactive itinerant process, during a presentation of SS, between mediators and students of Youth and Adult Education (EJA) deprived of freedom using, for registration, field diary, and photos. Two conversation wheels were also subsequently promoted with the mediators. Based on Vygotsky’s historical-cultural theory and the dialogical perspective for Paulo Freire,  we verified as results, from the analysis of the data, objective indications that participating in this process of itinerant scientific outreach in non-formal education, with scientific experiments, allowed an expansion of the didactic and methodological repertoire of mediators, the understanding of the particularities of work with youth and adult education, promoted the reflection on the role of itinerant scientific outreach and non-formal education in the process of approaching the population to scientific knowledge and also the importance of actions such as these in spaces of deprivation of liberty.